2015
DOI: 10.3171/2014.12.jns141031
|View full text |Cite
|
Sign up to set email alerts
|

Peritumoral cysts associated with pituitary macroadenoma

Abstract: OBJECT Peritumoral cysts are benign nonneoplastic cysts that are found adjacent to extraaxial brain tumors such as meningiomas, schwannomas, craniopharyngiomas, and esthesioneuroblastomas. Peritumoral cysts associated with pituitary macroadenomas have not been previously described in the literature. The authors report 6 cases of giant macroadenoma-associated peritumoral cysts and delineate their imaging spectrum. METHODS The authors retrospectively reviewed the records of 179 patients diagnosed with pituitary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Occasionally, the surgeon may encounter a peritumoral cyst associated with a giant pituitary macroadenoma. 35 These are benign, nonneoplastic fluid collections that likely represent proteinaceous CSF that has been trapped in a sulcus or cistern by anterolateral extension of the giant tumor. These cysts can be used by surgeons to facilitate dissection by providing a cleavage plane, and the resection of cysts is likely unnecessary (case 3).…”
Section: Tumor Growth Beyond Diaphragma Sellaementioning
confidence: 99%
See 1 more Smart Citation
“…Occasionally, the surgeon may encounter a peritumoral cyst associated with a giant pituitary macroadenoma. 35 These are benign, nonneoplastic fluid collections that likely represent proteinaceous CSF that has been trapped in a sulcus or cistern by anterolateral extension of the giant tumor. These cysts can be used by surgeons to facilitate dissection by providing a cleavage plane, and the resection of cysts is likely unnecessary (case 3).…”
Section: Tumor Growth Beyond Diaphragma Sellaementioning
confidence: 99%
“…These cysts can be used by surgeons to facilitate dissection by providing a cleavage plane, and the resection of cysts is likely unnecessary (case 3). 35 Despite the evidence for better outcome rates with regard to morbidity and visual outcomes with transsphenoidal surgery, the surgeon should keep in mind the limitations of visualization at surgical access to portions extending laterally beyond the carotid arteries. 1,2,7,13,23 Whereas traditional transsphenoidal microscopic techniques have the limitation of a longer working distance and distant illumination through the narrow corridor provided by the Hardy retractor, the use of the endoscope as an adjunct or on its own may provide optimal visualization of the tumor and increase the safety of the surgery.…”
Section: Tumor Growth Beyond Diaphragma Sellaementioning
confidence: 99%
“…Fluid signal suppression could help increase the contrast between cystic and solid portions. Some studies have reported that FLAIR improved tissue contrast in the presence of degenerative disease of the cervical spine area and brain lesions [10][11][12] . It has also been reported that there is a potential use for FLAIR imaging in patients with vascular malformations and to assess condylar bone marrow changes in temporomandibular joint disorders 14,15) .…”
Section: Discussionmentioning
confidence: 99%
“…Fluid-attenuated inversion recovery (FLAIR) imaging is an inversion recovery technique that suppresses the signal of pure water by setting the inversion time to the time at which the magnetization of pure water equals zero. FLAIR, an MRI sequence, has important roles in brain imaging [10][11][12] and has recently been used to examine pathological areas in the eye 13) . There are few reports, however, of the potential use of FLAIR in the oral and maxillofacial region 14,15) .…”
Section: Introductionmentioning
confidence: 99%